318 LONG-TERM BENEFICIAL EFFECTS OF ERYTHROPOIETIN GIVEN AFTER NEONATAL STROKE IN POSTNATAL DAY-7 RATS. (1st January 2005) - Wen, T. C.; Rogido, M.; Lee, B.; Thompson, R.; Genetta, T.; Sola, A.
Abstract : Background: We and others have shown that erythropoietin (Epo) attenuates neonatal brain injury caused by hypoxia-ischemia and neonatal stroke; however, little is known about the long-term effects of Epo on injury to the developing brain. Objective: To investigate the long-term effects of Epo on brain injury caused by focal cerebral ischemia (FCI) in postnatal day-7 (P7) rat pups. Methods: FCI was induced by using a modified intraluminal catheter technique causing middle cerebral artery occlusion in P7 rats, as previously described. The experimental groups included sham-operated (n = 15), FCI plus vehicle (n = 17) and FCI plus recombinant human Epo (n = 18). In Epo-treated group, pups received a single intraperitoneal injection of 1000 U/kg at 15 minutes after FCI, which was repeated at 1 and 2 days after FCI. At 6 and 12 weeks after surgery, animals were sacrificed, and body weight and brain weight were determined, and then their brains were cut into 2 mm coronal slices. The infarct area and volume were measured using Windows Image J. Statistical comparisons were conducted by using the two-tailed Mann-Whitney U-test. Results: In the vehicle-treated FCI group, focal cerebral insult caused a marked reduction in brain weight (6 weeks: 1.23 ± 0.1 g; 12 weeks: 1.50 ± 0.1 g; p = .0017), but there was no significant difference in body weight (6 weeks: 104.4 ± 13.7 g; 12 weeks: 352.0 ± 77.5 g), compared to the sham-operated group. Mean brain weight in the Epo-treated FCI group was significantly increased at 6 weeks (1.39 ± 0.1 g; p = .0015) and at 12 weeks (1.75 ± 0.14 g; p = .001) after FCI compared to the vehicle-treated group. Moreover, Epo treatment after FCI produced significant reductions in the mean infarct area and volume in comparison to vehicle-treated group at 6 weeks (infarct area: 38.2 ± 33.6 mm< vs 94.3 ± 23.4 mm<, p = .002; infarct volume: 67.8 ± 53.1 mm> vs 188.5 ± 46.9 mm>, p = .002) and at 12 weeks (infarct area: 67.4 ± 45.0 mm< vs 127.2 ± 21.9 mm<; infarct volume: 134.9 ± 89.9 mm> vs 253.3 ± 44.2 mm>). Conclusion: Epo administration after focal cerebral insult produces a significant neuroprotective benefit over a prolonged period in the developing rat brain with neonatal stroke. These findings indicate that Epo may indeed be of clinical use as a potential neuroprotective agent in neonatal ischemic injury.